Day length and weather conditions profoundly affect physical activity levels in older functionally impaired people. Issue 4 (11th December 2008) - Sumukadas, D; Witham, M; Struthers, A; McMurdo, M
Abstract : Background: Regular physical activity is vital for maintaining the health and independence of older people. Few objective data exist on the effect of weather on physical activity levels in this group. The objective of this study was to evaluate the effect of weather using an objective measure of physical activity. Methods: This was a retrospective study of 127 participants, >65 years old, who were enrolled in a previous randomised controlled trial. The main outcome was daily activity counts measured using the RT3 triaxial accelerometer over 1-week periods. These were correlated with local weather data including daily maximum temperature, sunshine, precipitation and wind speed that were obtained from the metrological office. Results: The mean age of the subjects was 78.6 years; 90/127 were female; and 720 usable daily counts were obtained for the 127 participants. The mean daily counts showed a striking seasonal variation, with maximum activity in June and minimum in February (137 557 vs 65 010 counts per day, p<0.001). Day length, mean maximum temperature and mean daily sunshine were able to explain 72.9% of the monthly variance in daily activity levels. Daily counts showed moderate correlation with day length (r = 0.358, p<0.001), maximum temperature (r = 0.345, p<0.001), duration of sunshine (r = 0.313, p<0.001) and rain (r = −0.098, p = 0.008) but not with wind speed (r = 0.093, p = 0.12). Multivariate analysis showed that day length, sunshine duration and maximum temperature were independent predictors of daily activity (adjusted R 2  = 0.16). Conclusions: Physical activity levels among older people are much higher in summer than in winter. Day length, sunshine duration and maximum temperature have a significant influence on physical activity levels.